2014
DOI: 10.1016/j.actatropica.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of 5-fluorouracil and paclitaxel on Echinococcus granulosus larvae and cells

Abstract: Human cystic echinococcosis is a zoonosis caused by the metacestode stage of the tapeworm Echinococcus granulosus. Although benzimidazole compounds such as albendazole and mebendazole have been the cornerstone of chemotherapy for the disease, there is often no complete recovery after treatment. Hence, in searching for novel treatment options, we examined the in vitro efficacies of 5-fluorouracil (5-FU) and paclitaxel (PTX) against E. granulosus germinal cells, protoscoleces and cysts. 5-FU or PTX inhibited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…When infecting humans, Echinococcus granulosus, Echinococcus multilocularis, Echinococcus oligarthrus, and Echinococcus vogeli are localized in the liver (in 75% of cases), the lungs (in 5-15% of cases), and other organs such as the spleen, brain, heart, and kidneys (in 10-20% of cases). Paclitaxel with 5fluorouracil at dose 1-10 μg/mL effectively inhibited the growth of E. granulosus (Pensel et al, 2014). It was suggested that paclitaxel may act by arresting both interphase and mitotic cell cycle phases in E. granulosus.…”
Section: Resultsmentioning
confidence: 99%
“…When infecting humans, Echinococcus granulosus, Echinococcus multilocularis, Echinococcus oligarthrus, and Echinococcus vogeli are localized in the liver (in 75% of cases), the lungs (in 5-15% of cases), and other organs such as the spleen, brain, heart, and kidneys (in 10-20% of cases). Paclitaxel with 5fluorouracil at dose 1-10 μg/mL effectively inhibited the growth of E. granulosus (Pensel et al, 2014). It was suggested that paclitaxel may act by arresting both interphase and mitotic cell cycle phases in E. granulosus.…”
Section: Resultsmentioning
confidence: 99%
“…The proteasome inhibitor, bortezomib, which was developed for myeloma chemotherapy, displays high activity against E. multilocularis metacestodes in vitro although the activity of this drug was lower than that of albendazole and induced adverse effects in vivo [ 5 ]. Furthermore, 5-fluorouracil and paclitaxel [ 6 ], as well as imatinib [ 7 ], exhibit profound anti-parasitic activity against E. multilocularis . These results suggest that novel candidate drugs for the treatment of CE might be found among the chemicals with antitumor effects.…”
Section: Introductionmentioning
confidence: 99%
“…The PSCs were separated in sterile conditions and washed three times in phosphate-buffered saline (PBS). Rinsed PSCs were diluted to a concentration of 1,500 mL −1 and maintained as previously described 33, 47 . Briefly, PSCs were cultured in RPMI 1640 medium (Hyclone) with 10% fetal bovine serum (Hyclone), 10% hydatid fluid, 100 U.mL −1 penicillin G and 100 μg.mL −1 streptomycin (Sigma, USA).…”
Section: Methodsmentioning
confidence: 99%